К вопросу о рационе административного персонала государства эпохи III династии Ура - Шарашенидзе, Дж. M.
Šarašenidze, Dž. M., The Rations of State Administrative Personnel in the Epoch of the Third Dynasty of Ur; engl. Résumé.